Analysis of Facility Surveillance System by Tata Terminal Unit at Juwata Tarakan International Airport, North Kalimantan - Nurellyna Marhani; Faiz Albana (CV. Rayyan Dwi Bharata, 2023)
The terminal is a liaison between land transportation and air transportation systems that accommodate all departure process activities from the transfer of passengers to goods. Passenger terminals must be able to accommodate operational activities and must meet operational security and safety requirements. In addition to taking part in the processing of existing activities, ensuring passenger comfort in using facilities is also important. Supervision of facilities can have a major impact on the safety and comfort of airport service users. The approach with qualitative methods is the approach that will be applied in this study. Qualitative research is research used to describe, explain, investigate, and find the quality of influence that cannot be explained, measured or described through a quantitative approach. The data obtained is in the form of research observations located at Juwata Tarakan International Airport, interviews with Tata Terminal Unit officers, and documentation. Data analysis techniques used include data collection, data reduction, and conclusions. The results of this study show that in supervising facilities at Juwata Tarakan International Airport there are still several obstacles experienced by Tata Terminal Unit officers, especially in terms of coordination and cooperation between Tata Terminal Unit and other units which are considered to have an impact on the satisfaction services provided at Juwata Tarakan International Airport.